A Normative Argument Towards the Independence of Public Debt Management - Tsintzos, Panagiotis; Efthimiadis, Tilemahos; Papadamou, Stephanos; Spyromitros, Eleftherios (Review of Economic Analysis, 2023)
We explore the links between credit expansion, inflation, and inflation expectations, and show that active public debt management can trigger a non-interest rate channel of credit expansion. This creates incentives for the government to use debt management for promoting non-debt management goals, thus, choosing debt maturity structure that differs from its optimal. Through a theoretical monetary policy game, we show that it is welfare improving to delegate public debt management to an independent office separate from the fiscal authority.